NiqÄt al-IltiqÄâ€™ bayn Madhhad al-Taá¸¥dÄ«th al-JadÄ«d wa al-IttijÄh al-TaqlÄ«dÄ« al-Mutaá¹awwir al-JudhÅ«r al-Maâ€™rifÄ«yah li Madhhab al-JawharÄ«yah al-IslÄmÄ«yah wa IntishÄruhÄfÄ« IndÅ«nÄ«sÄ«yÄ - Ala, Abdul (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2004)
The roots of neos-modernism- a school of thought in Islam that was succesfull in Indonesia in the 1980s-strongly relate to Islamic liberalism. This reality requires us to link recent discussions about liberal Islamic discourse with discussions on neo-modernism.Â The issue modernism must be addressed, because it is able to attract the attention of leaders of the Islamic community from various school of thought.DOI:Â 10.15408/sdi.v11i1.654